Ekonomi Sirkular Sebagai Antitesis Dari Ekonomi Linier : Sebuah Tinjauan - Lola Malihah; Magfiroh, Siti (Jurnal Ekonomi STIEP, 2024)
Environmental conditions that are damaged as a result of economic activities make the world community have taken into account the environment as a part that needs serious attention in economic activities and sustainable development. One of the economic models offered to the world is the circular economy model, where in this model goods that have been consumed can be reprocessed. This paper is a literature review that aims to examine the concept of circular economy, a new economic concept that is considered environmentally friendly and in line with sustainable development. The circular economy in its implementation does not only focus on making products, selling and consuming them, but the circular economy also pays attention to the rest of the products after useLooking at environmental conditions as a result of economic activity, world economists have taken into account the environment as a part that needs serious attention in economic activity and sustainable development. One of the economic models offered to the world is the circular economy model, where in this model goods that have been consumed can be reprocessed. This paper is a literature review that aims to examine the concept of circular economy, a new economic concept that is considered environmentally friendly and in line with sustainable development. The circular economy in its implementation does not only focus on making products, selling and consuming them, but the circular economy also pays attention to the rest of the products after use. Where from the products that have been consumed it is not allowed to become waste, but can be used again as raw material to make new products, so it is hoped that there will be no more leftover products into unused waste. The concept of circular economy is certainly a refutation of the concept of linear economy that has been carried out so far, where companies only focus on making products, selling and then consuming and ending up with product waste. With environmental conditions, climate change and global warming as it is today, the concept of circular economy is a solution that must be applied where economic activities continue but environmental improvement efforts can also be implemented.